2016
DOI: 10.1007/s12208-016-0154-y
|View full text |Cite
|
Sign up to set email alerts
|

Word-of-mouth in the health care sector: a literature analysis of the current state of research and future perspectives

Abstract: Health care is a tremendously expensive service that deeply impacts the daily life of individuals. It has become crucial to understand all the factors that influence the usage of these services. Word-of-mouth (WOM) is such a factor, because it strongly affects the health behavior. A research gap exists when it comes to the analysis of the current state of WOM research in the health care sector. Based on a comprehensive literature review of the leading scientific journals in the health care sector, this paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 60 publications
3
74
0
2
Order By: Relevance
“…A nationally representative survey of U.S. adults revealed that 85% of respondents reported that WOM recommendations from family or friends were a very important or at least somewhat important factor when choosing their physician (Hanauer, Zheng, Singer, Gebremariam, & Davis, ). Similar studies have also demonstrated the importance of WOM recommendations when choosing hospitals (De Cruppé & Geraedts, ; Martin, ); primary care physicians (Tu & Lauer, ); surgeons (Yahanda, Lafaro, Spolverato, & Pawlik, ); cancer specialists (Jiang et al, ); and other types of healthcare providers and resources (McCaughey, McGhan, Walsh, Rathert, & Belue, ; Pettigrew & Durrance, ; Shreffler‐Grant, Weinert, Nichols, & Ide, ). Individuals can draw out highly experiential insights from their family, friends and acquaintances around their satisfaction and dissatisfaction on a wide array of points of care, such as cost, clinical competencies, staff members' interpersonal skills, and more (Martin, ).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…A nationally representative survey of U.S. adults revealed that 85% of respondents reported that WOM recommendations from family or friends were a very important or at least somewhat important factor when choosing their physician (Hanauer, Zheng, Singer, Gebremariam, & Davis, ). Similar studies have also demonstrated the importance of WOM recommendations when choosing hospitals (De Cruppé & Geraedts, ; Martin, ); primary care physicians (Tu & Lauer, ); surgeons (Yahanda, Lafaro, Spolverato, & Pawlik, ); cancer specialists (Jiang et al, ); and other types of healthcare providers and resources (McCaughey, McGhan, Walsh, Rathert, & Belue, ; Pettigrew & Durrance, ; Shreffler‐Grant, Weinert, Nichols, & Ide, ). Individuals can draw out highly experiential insights from their family, friends and acquaintances around their satisfaction and dissatisfaction on a wide array of points of care, such as cost, clinical competencies, staff members' interpersonal skills, and more (Martin, ).…”
Section: Introductionmentioning
confidence: 84%
“…The concept of eWOM generally refers to consumer‐generated content posted and viewed on social networking sites (SNSs) to provide and garner emotional and information support from other individuals (Liang & Scammon, ). eWOM communication may help individuals overcome the geographic and synchronous communication limitations of traditional WOM recommendations for hospitals and healthcare providers (Martin, ). However, eWOM recommendations may not have the same level of reliability and credibility as recommendations individuals receive from their family members, friends, and other individuals in their co‐located informal social networks (Huete‐Alcocer, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a positive patient experience is a priority in itself, it is also important because it improves correct family planning method use, contraceptive continuation rates, and consistent use of health services 2 . The importance of a positive experience is amplified when considering the role of word-of-mouth referrals in marketing strategies 3 and the potential for generating demand for family planning services in countries with low modern contraceptive prevalence rates (mCPRs).…”
Section: Introductionmentioning
confidence: 99%